2018
DOI: 10.1021/acs.analchem.8b02438
|View full text |Cite
|
Sign up to set email alerts
|

New Electrochemical Flow-Cell Configuration Integrated into a Three-Dimensional Microfluidic Platform: Improving Analytical Application in the Presence of Air Bubbles

Abstract: A newly configured electrochemical flow cell to be used for (end-channel) amperometric detection in a microfluidic device is presented. The design was assembled to place the reference electrode in a separated compartment, isolated from the flow in the microchannel, while the working and counter electrodes remain in direct contact with both compartments. Moreover, a three-dimensional coil-shaped microfluidic device was fabricated using a nonconventional protocol. Both devices working in association enabled us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several reviews have been published over recent years about the plenitude of microfluidics application [153,154,155,156,157], although, in light of this review, the development of microfluidics chips to detect microorganisms are the most relevant [152,158,159,160]. Detection of pathogenic bacteria and viruses using Chips is possible by recurring small sample volumes with great sensitivity, and it has huge applicability in food safety control, environmental monitoring, and clinical diagnosis.…”
Section: Biochemical Analytical Methods To Detect Microorganismsmentioning
confidence: 99%
“…Several reviews have been published over recent years about the plenitude of microfluidics application [153,154,155,156,157], although, in light of this review, the development of microfluidics chips to detect microorganisms are the most relevant [152,158,159,160]. Detection of pathogenic bacteria and viruses using Chips is possible by recurring small sample volumes with great sensitivity, and it has huge applicability in food safety control, environmental monitoring, and clinical diagnosis.…”
Section: Biochemical Analytical Methods To Detect Microorganismsmentioning
confidence: 99%
“…Lastly, the research fields of microfluidics and electrochemistry are also frequently linked for electrochemical sensing purposes for which microfluidic analytical devices may be constructively employed. Examples of such contributions include microfluidic sensors or detectors that rely on electrochemical sensing applied for sensing labeled particles or detecting analytes such as lactate, , dopamine, , or toxins . These works however do not focus on energy conversion and are therefore generally beyond the scope of this review.…”
Section: Devices and Applicationsmentioning
confidence: 99%
“…Relying on the versatile green BODIPY fluorophore, our approach can not only be automatized, but also combined with other BODIPY-based indicators, opening new prospects for multiparameter online sensing with simple optical detection setups. Regarding 3D chip design, we have shown that opto-microfluidic chips manufactured by 3D printing of ABS show superior performance over conventional layouts, a first example for electrochemical chips having been reported lately, 74 and that the microhydrocyclone design is suitable for eliminating detrimental effects of random gas bubble formation, which is an intrinsic feature of the chemical analysis of real samples with unknown analyte content generating gaseous species in the reaction between probe and analyte. Current research in our laboratory is directed toward a miniaturized multiparameter device for water analysis.…”
Section: Analytical Chemistrymentioning
confidence: 99%